Specificity of anti-lymphocyte antibodies in sera from patients with AIDS-related complex (ARC) and healthy homosexuals. - Warren, R Q (1988)
The presence and specificity of anti-lymphocyte antibodies (ALA) was investigated in sera from male homosexuals with AIDS-Related Complex (ARC) as well as healthy homosexuals. Individuals in the healthy homosexual group had no detectable antibodies to human immunodeficiency virus (HIV). Antibodies reactive with normal peripheral blood mononuclear cells were detected by Western blot analysis in sera from both groups of homosexuals. Of those individuals whose sera contained ALA, 71% of ARC patients and 83% of healthy homosexuals had antibodies recognizing a 73 kilodalton (kD) molecule. ALA present in ARC sera reacted with CD3+, CD4+ and CD8+ lymphocytes while little reactivity with B cells was observed. Our results indicate that ALA appear in homosexuals prior to HIV infection and are reactive primarily with T lymphocytes. A 73 kD structure associated with the T cell membrane is frequently the target for these antibodies.